2009
DOI: 10.1089/thy.2008.0392
|View full text |Cite
|
Sign up to set email alerts
|

Second Primary Malignancy Risk After Radioactive Iodine Treatment for Thyroid Cancer: A Systematic Review and Meta-analysis

Abstract: The risk of SPMs in thyroid cancer survivors treated with RAI is slightly increased compared to thyroid cancer survivors not treated with RAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
183
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(196 citation statements)
references
References 23 publications
(87 reference statements)
7
183
0
6
Order By: Relevance
“…Megállapították, hogy a hyperthyreosis radiojódkezelését követően ilyen veszélytől nem kell tartani [45]. A pajzsmirigyrákok jód-izotópos kezelésekor azonban sokkal nagyobb dózisokra van szükség, mint hyperthyreosisban (akár 10-szer nagyobb adagokról van szó), ezeknél az SPM előfordulásá-nak veszélye nem hanyagolható el és mindenképpen nagyobb, mint a radiojóddal nem kezelteken [46]. Svéd, olasz és francia területről gyűjtött betegadatokban 6841 pajzsmirigyrákos 131 I-dal kezelt betegről van szó.…”
Section: A Radiojódterápia Késői Mellékhatásaiunclassified
“…Megállapították, hogy a hyperthyreosis radiojódkezelését követően ilyen veszélytől nem kell tartani [45]. A pajzsmirigyrákok jód-izotópos kezelésekor azonban sokkal nagyobb dózisokra van szükség, mint hyperthyreosisban (akár 10-szer nagyobb adagokról van szó), ezeknél az SPM előfordulásá-nak veszélye nem hanyagolható el és mindenképpen nagyobb, mint a radiojóddal nem kezelteken [46]. Svéd, olasz és francia területről gyűjtött betegadatokban 6841 pajzsmirigyrákos 131 I-dal kezelt betegről van szó.…”
Section: A Radiojódterápia Késői Mellékhatásaiunclassified
“…In 2003, Rubino et al [37] reported that cumulative doses of RAI (Ͼ600 MCi, 22 GBq) are associated with a higher risk for leukemia. A greater risk for other secondary malignancies has also been reported [38,39]. Thus, the use of RAI should be individualized to balance the risks against the therapeutic benefit.…”
Section: Raimentioning
confidence: 99%
“…But, most long-term follow-up studies report a very low risk of secondary malignancies in long-term survivors (Rubino et al, 2003;Brown et al, 2008). Howewer, meta-analysis of two large multicenter studies showed that the risk of second malignancies was significantly increased relative to thyroid cancer survivors not treated with RAI (Sawka et al, 2009). The risk of secondary malignancies is dose related (Rubino et al, 2003), Cumulative 131 I activities above 500-600 mCi are associated with a significant increase in risk.…”
Section: Introductionmentioning
confidence: 99%